Bilateral Tuberculum Sextum of Maxillary Permanent First Molar - Mrunali Prashant Deshkar; Yash Naik; Ramakrishna Yeluri; Nilima Thosar; Monika Khubchandani; Meenal Pande (Diagnostics)
The human tooth’s morphology, which includes variations in cusp numbers and patterns, is of tremendous interest to anthropologists, morphologists, and dentists. Cusp 6 is an additional cusp that is very seldom encountered in primary or permanent mandibular molars, especially first molars. A supernumerary cusp located lingual to the distobuccal cusp at the crown’s distal border is cusp 6. According to the literature, cusp 6 is also known by other anthropologic designations, such as “Tuberculum Sextum” or “Entoconulid”. This case offers a unique instance of a bilateral tuberculum sextum in the maxillary permanent first molars, characterized by an additional cusp on the lingual surface. The patient, an adolescent, exhibited no associated symptoms. Early detection of such dental anomalies is essential for treatment planning, particularly in maintaining occlusal balance and preventing future complications. Regular monitoring is necessary to manage a bilateral tuberculum sextum in order to avoid enamel fractures and occlusal interference. To preserve functional occlusion and avoid problems, prophylactic sealants or selective grinding may be taken into consideration. This report highlights the importance of recognizing a tuberculum sextum for proper clinical management.